Accuracy and completeness of drug information in Wikipedia: a comparison with standard textbooks of pharmacology - Kraeenbring, Jona; Penza, Tika Monzon; Gutmann, Joanna; Muehlich, Susanne; Zolk, Oliver; Wojnowski, Leszek; Maas, Renke; Engelhardt, Stefan; Sarikas, Antonio (PLoS ONE, 2014)
The online resource Wikipedia is increasingly used by students for knowledge acquisition and learning. However, the lack of a formal editorial review and the heterogeneous expertise of contributors often results in skepticism by educators whether Wikipedia should be recommended to students as an information source. In this study we systematically analyzed the accuracy and completeness of drug information in the German and English language versions of Wikipedia in comparison to standard textbooks of pharmacology. In addition, references, revision history and readability were evaluated. Analysis of readability was performed using the Amstad readability index and the Erste Wiener Sachtextformel. The data on indication, mechanism of action, pharmacokinetics, adverse effects and contraindications for 100 curricular drugs were retrieved from standard German textbooks of general pharmacology and compared with the corresponding articles in the German language version of Wikipedia. Quantitative analysis revealed that accuracy of drug information in Wikipedia was 99.7% ± 0.2% when compared to the textbook data. The overall completeness of drug information in Wikipedia was 83.8 ± 1.5% (p < 0.001). Completeness varied in-between categories, and was lowest in the category "pharmacokinetics" (68.0% ± 4.2%; p < 0.001) and highest in the category "indication" (91.3% ± 2.0%) when compared to the textbook data overlap. Similar results were obtained for the English language version of Wikipedia. Of the drug information missing in Wikipedia, 62.5% was rated as didactically non-relevant in a qualitative re-evaluation study. Drug articles in Wikipedia had an average of 14.6 ± 1.6 references and 262.8 ± 37.4 edits performed by 142.7 ± 17.6 editors. Both Wikipedia and textbooks samples had comparable, low readability. Our study suggests that Wikipedia is an accurate and comprehensive source of drug-related information for undergraduate medical education.
EVALuna2:8687

Actin-mediated gene expression depends on RhoA and Rac1 signaling in proximal tubular epithelial cells - Giehl, Klaudia; Keller, Christof; Muehlich, Susanne; Goppelt-Strübe, Margarete (PLoS ONE, 2015)
Morphological alterations of cells can lead to modulation of gene expression. An essential link is the MKL1-dependent activation of serum response factor (SRF), which translates changes in the ratio of G- and F-actin into mRNA transcription. SRF activation is only partially characterized in non-transformed epithelial cells. Therefore, the impact of GTPases of the Rho family and changes in F-actin structures were analyzed in renal proximal tubular epithelial cells. Activation of SRF signaling was compared to the regulation of a known MKL1/SRF target gene, connective tissue growth factor (CTGF). In the human proximal tubular cell line HKC-8 overexpression of two actin mutants either favoring or preventing the formation of F-actin fibers regulated SRF-mediated transcription as well as CTGF expression. Only overexpression of constitutively active RhoA activated SRF-dependent gene expression whereas no effect was detected upon overexpression of Rac1 mutants. To elucidate the functional role of Rho kinases as downstream mediators of RhoA, pharmacological inhibition and genetic inhibition by transient siRNA knock down were compared. Upon stimulation with lysophosphatidic acid (LPA) Rho kinase inhibitors partially suppressed SRF-mediated transcription, whereas interference with Rho kinase expression by siRNA reduced activation of SRF, but barely affected CTGF expression. Together with the partial inhibition of CTGF expression by the pharmacological inhibitors Y27432 and H1154, Rho kinases seem to be less important in mediating RhoA signaling related to CTGF expression in HKC-8 epithelial cells. Short term pharmacological inhibition of Rac1 activity by EHT1864 reduced SRF-dependent CTGF expression in HKC-8 cells, but was overcome by a stimulatory effect after prolonged incubation after 4-6 h. Similarly, human primary cells of proximal but not of distal tubular origin showed inhibitory as well as stimulatory effects of Rac1 inhibition. Thus, RhoA signaling activates MKL1-SRF-mediated CTGF expression in proximal tubular cells, whereas Rac1 signaling is more complex with adaptive cellular responses.
EVALuna2:3783

A novel inhibitory mechanism of MRTF-A/B on the ICAM-1 gene expression in vascular endothelial cells - Hayashi, Ken'Ichiro; Murai, Toshiyuki; Oikawa, Hiroki; Masuda, Tomoyuki; Kimura, Kazuhiro; Muehlich, Susanne; Prywes, Ron; Morita, Tsuyoshi (Scientific Reports, 2015)
The roles of myocardin-related transcription factor A (MRTF-A) and MRTF-B in vascular endothelial cells are not completely understood. Here, we found a novel regulatory mechanism for MRTF-A/B function. MRTF-A/B tend to accumulate in the nucleus in arterial endothelial cells in vivo and human aortic endothelial cells (HAoECs) in vitro. In HAoECs, nuclear localization of MRTF-A/B was not significantly affected by Y27632 or latrunculin B, primarily due to the reduced binding of MRTF-A/B to G-actin and in part, to the low level of MRTF-A phosphorylation by ERK. MRTF-A/B downregulation by serum depletion or transfection of siRNA against MRTF-A and/or MRTF-B induced ICAM-1 expression in HAoECs. It is known that nuclear import of nuclear factor κ B (NFκ B) plays a key role in ICAM-1 gene transcription. However, nuclear accumulation of NFκ B p65 was not observed in MRTF-A/B-depleted HAoECs. Our present findings suggest that MRTF-A/B inhibit ICAM-1 mRNA expression by forming a complex with NFκ B p65 in the nucleus. Conversely, downregulation of MRTF-A/B alleviates this negative regulation without further translocation of NF κB p65 into the nucleus. These results reveal the novel roles of MRTF-A/B in the homeostasis of vascular endothelium.
CRIS-Team Scopus Importer:2024-07-10

ATF2 loss promotes tumor invasion in colorectal cancer cells via upregulation of cancer driver TROP2 - Hübner, Kerstin; Erlenbach-Wünsch, Katharina; Prochazka, Jan; Sheraj, Ilir; Hampel, Chuanpit; Mrazkova, Blanka; Michalcikova, Tereza; Tureckova, Jolana; Iatsiuk, Veronika; Weissmann, Anne; Ferrazzi, Fulvia; Kunze, Philipp; et al. (Cellular and Molecular Life Sciences, 2022)
In cancer, the activating transcription factor 2 (ATF2) has pleiotropic functions in cellular responses to growth stimuli, damage, or inflammation. Due to only limited studies, the significance of ATF2 in colorectal cancer (CRC) is not well understood. We report that low ATF2 levels correlated with worse prognosis and tumor aggressiveness in CRC patients. NanoString gene expression and ChIP analysis confirmed trophoblast cell surface antigen 2 (TROP2) as a novel inhibitory ATF2 target gene. This inverse correlation was further observed in primary human tumor tissues. Immunostainings revealed that high intratumoral heterogeneity for ATF2 and TROP2 expression was sustained also in liver metastasis. Mechanistically, our in vitro data of CRISPR/Cas9-generated ATF2 knockout (KO) clones revealed that high TROP2 levels were critical for cell de-adhesion and increased cell migration without triggering EMT. TROP2 was enriched in filopodia and displaced Paxillin from adherens junctions. In vivo imaging, micro-computer tomography, and immunostainings verified that an ATF2(KO)/TROP2(high) status triggered tumor invasiveness in in vivo mouse and chicken xenograft models. In silico analysis provided direct support that ATF2(low)/TROP2(high) expression status defined high-risk CRC patients. Finally, our data demonstrate that ATF2 acts as a tumor suppressor by inhibiting the cancer driver TROP2. Therapeutic TROP2 targeting might prevent particularly the first steps in metastasis, i.e., the de-adhesion and invasion of colon cancer cells.
CRIS-Team WoS Importer:2022-07-29

Depletion of the transcriptional coactivators megakaryoblastic leukaemia 1 and 2 abolishes hepatocellular carcinoma xenograft growth by inducing oncogene-induced senescence - Hampl, Veronika; Martin, Claudia; Aigner, Achim; Hoebel, Sabrina; Singer, Stephan; Frank, Natalie; Sarikas, Antonio; Ebert, Oliver; Prywes, Ron; Gudermann, Thomas; Muehlich, Susanne (Embo Molecular Medicine, 2013)
Megakaryoblastic leukaemia 1 and 2 (MKL1/2) are coactivators of the transcription factor serum response factor (SRF). Here, we provide evidence that depletion of MKL1 and 2 abolishes hepatocellular carcinoma (HCC) xenograft growth. Loss of the tumour suppressor deleted in liver cancer 1 (DLC1) and the subsequent activation of RhoA were prerequisites for MKL1/2 knockdown-mediated growth arrest. We identified oncogene-induced senescence as the molecular mechanism underlying the anti-proliferative effect of MKL1/2 knockdown. MKL1/2 depletion resulted in Ras activation, elevated p16 expression and hypophosphorylation of the retinoblastoma (Rb) protein in DLC1-deficient HCC cells. Interestingly, reconstitution of HuH7 HCC cells with DLC1 also induced senescence. Evaluation of the therapeutic efficacy of MKL1/2 knockdown in vivo revealed that systemic treatment of nude mice bearing HuH7 tumour xenografts with MKL1/2 siRNAs complexed with polyethylenimine (PEI) completely abolished tumour growth. The regression of the xenografts was associated with senescence. Importantly, PEI-complexed MKL1 siRNA alone was sufficient for complete abrogation of HCC xenograft growth. Thus, MKL1/2 represent promising novel therapeutic targets for the treatment of HCCs characterized by DLC1 loss. © 2013 The Authors. Published by John Wiley and Sons, Ltd on behalf of EMBO.
CRIS-Team Scopus Importer:2024-07-10
Keywords: DLC1; MKL1; MKL2; MRTF; Senescence

Detection and quantification of cellular senescence in human melanocytes and melanoma cell lines - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Detection of Cellular Senescence in Human Primary Melanocytes and Malignant Melanoma Cells In Vitro - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (Cells, 2022)
Detection and quantification of senescent cells remain difficult due to variable phenotypes and the absence of highly specific and reliable biomarkers. It is therefore widely accepted to use a combination of multiple markers and cellular characteristics to define senescent cells in vitro. The exact choice of these markers is a subject of ongoing discussion and usually depends on objective reasons such as cell type and treatment conditions, as well as subjective considerations including feasibility and personal experience. This study aims to provide a comprehensive comparison of biomarkers and cellular characteristics used to detect senescence in melanocytic systems. Each marker was assessed in primary human melanocytes that overexpress mutant BRAFV600E, as it is commonly found in melanocytic nevi, and melanoma cells after treatment with the chemotherapeutic agent etoposide. The combined use of these two experimental settings is thought to allow profound conclusions on the choice of senescence biomarkers when working with melanocytic systems. Further, this study supports the development of standardized senescence detection and quantification by providing a comparative analysis that might also be helpful for other cell types and experimental conditions.
CRIS-Team Scopus Importer:2022-05-13
Keywords: beta-galactosidase; melanocyte; melanoma; senescence

Evidence for a regulatory role of Cullin-RING E3 ubiquitin ligase 7 in insulin signaling - Scheufele, Florian; Wolf, Benjamin; Kruse, Michael; Hartmann, Thomas; Lempart, Justine; Muehlich, Susanne; Pfeiffer, Andreas F.H.; Field, Loren J.; Charron, Maureen J.; Pan, Zhen Qiang; Engelhardt, Stefan; Sarikas, Antonio (Cellular Signalling, 2014)
Dysfunctional regulation of signaling pathways downstream of the insulin receptor plays a pivotal role in the pathogenesis of insulin resistance and type 2 diabetes. In this study we report both in vitro and in vivo experimental evidence for a role of Cullin-RING E3 ubiquitin ligase 7 (CRL7) in the regulation of insulin signaling and glucose homeostasis. We show that Cul7-/- mouse embryonic fibroblasts displayed enhanced AKT and Erk MAP kinase phosphorylation upon insulin stimulation. Depletion of CUL7 by RNA interference in C2C12 myotubes led to increased activation of insulin signaling pathways and cellular glucose uptake, as well as a reduced capacity of these cells to execute insulin-induced degradation of insulin receptor substrate 1 (IRS1). In vivo, heterozygosity of either Cul7 or Fbxw8, both key components of CRL7, resulted in elevated PI3 kinase/AKT activation in skeletal muscle tissue upon insulin stimulation when compared to wild-type controls. Finally, Cul7+/- or Fbxw8+/- mice exhibited enhanced insulin sensitivity and plasma glucose clearance. Collectively, our findings point to a yet unrecognized role of CRL7 in insulin-mediated control of glucose homeostasis by restraining PI3 kinase/AKT activities in skeletal muscle cells. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2024-07-10
Keywords: Cell signaling; E3 ubiquitin ligase; Insulin; Proteasome; Ubiquitin

Filamin A interacts with the coactivator MKL1 to promote the activity of the transcription factor SRF and cell migration - Kircher, Philipp; Hermanns, Constanze; Nossek, Maximilian; Drexler, Maria Katharina; Grosse, Robert; Fischer, Maximilian; Sarikas, Antonio; Penkava, Josef; Lewis, Thera; Prywes, Ron; Gudermann, Thomas; Muehlich, Susanne (Science Signaling, 2015)
Megakaryoblastic leukemia 1 (MKL1) is a coactivator of serum response factor (SRF) that promotes the expression of genes associated with cell proliferation, motility, adhesion, and differentiation-processes that also involve dynamic cytoskeletal changes in the cell. MKL1 is inactive when bound to monomeric globular actin (G-actin), but signals that activate the small guanosine triphosphatase RhoA cause actin polymerization and MKL1 dissociation from G-actin. We found a new mechanism of MKL1 activation that is mediated through its binding to filamin A (FLNA), a protein that binds filamentous actin (F-actin). The interaction of FLNA and MKL1 was required for the expression of MKL1 target genes in primary fibroblasts, melanoma, mammary and hepatocellular carcinoma cells. We identified the regions of interaction between MKL1 and FLNA, and cells expressing an MKL1mutant that was unable to bind FLNA exhibited impaired cell migration and reduced expression of MKL1-SRF target genes. Induction and repression of MKL1-SRF target genes correlated with increased or decreased MKL1-FLNA interaction, respectively. Lysophosphatidic acid- induced RhoA activation in primary human fibroblasts promoted the association of endogenous MKL1 with FLNA, whereas exposure to an actin polymerization inhibitor dissociated MKL1 from FLNA and decreased MKL1-SRF target gene expression in melanoma cells. Thus, FLNA functions as a positive cellular transducer linking actin polymerization toMKL1-SRF activity, counteracting the known repressive complex of MKL1 and monomeric G-actin.
CRIS-Team Scopus Importer:2024-07-10

Identification of novel inhibitors of the transcriptional coactivator MRTF-A for HCC therapy - Franz, Miriam; Wenisch, Pia; Wohlleben, Petra; Rupprecht, Laura; Chubanov, Vladimir; Gudermann, Thomas; Kyheröinen, Salla; Vartiainen, Maria Kristina; Heinrich, Markus; Mühlich, Susanne (Molecular Therapy Oncology, 2024)
Myocardin-related transcription factor A (MRTF-A) is a coactivator of serum response factor (SRF), which regulates the expression of genes involved in cell proliferation, migration, and differentiation and has been implicated in hepatocellular carcinoma (HCC) progression. We recently established inhibition of the transcriptional activity of MRTF-A by NS8593 as a novel therapeutic approach for HCC therapy. NS8593 is a negative gating modulator of the transient receptor potential cation channel TRPM7. In this report, we identify an aminobenzimidazole that is highly potent in inhibiting TRPM7 and its interaction with RhoA, leading to decreased SRF transcriptional activity and enhanced nuclear export of MRTF-A, as determined by fluorescence loss in photobleaching (FLIP). This resulted in reduced expression of the MRTF/SRF target genes transforming growth factor β1 (TGF-β1) and tetraspanin 5 (TSPAN5), senescence induction, and growth arrest in HCC cells. Replacement of the tetraline core by a 3-aminophenyl substructure yielded inhibitor 10 with higher potency than inhibitor 5, and further structural modifications yielded highly potent inhibitors of SRF activity, 14 and 16. Both compounds were capable of inhibiting cell proliferation and inducing senescence in HCC cells with improved efficacy compared to NS8593. These inhibitors represent valuable tools for understanding the molecular basis of drug development targeting TRPM7 and MRTFs.
CRIS-Team Scopus Importer:2024-11-08
Keywords: HCC; MKL1; MRTF; MT: Regular Issue; NS8593; RhoA; SK; SRF; TGF-ß1; TRPM7; TSPAN5

Identification of the negative gating modulator of the transient receptor potential cation channel TRPM7 NS8593 as a novel inhibitor of MRTF/SRF-dependent gene expression and hepatocarcinogenesis - Voringer, S.; Zierler, S.; Chubanov, V.; Gudermann, T.; Mühlich, Susanne (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2019)
CRIS-Team WoS Importer:2019-02-21

Inhibition of Cullin-RING E3 ubiquitin ligase 7 by simian virus 40 large T antigen - Hartmann, Thomas; Xu, Xinsong; Kronast, Mira; Muehlich, Susanne; Meyer, Kathleen; Zimmermann, Wolfgang; Hurwitz, Jerard; Pan, Zhen Qiang; Engelhardt, Stefan; Sarikas, Antonio (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Simian virus 40 (SV40) large tumor antigen (LT) triggers oncogenic transformation by inhibition of key tumor suppressor proteins, including p53 and members of the retinoblastoma family. In addition, SV40 transformation requires binding of LT to Cullin 7 (CUL7), a core component of Cullin-RING E3 ubiquitin ligase 7 (CRL7). However, the pathomechanistic effects of LT-CUL7 interaction are mostly unknown. Here we report both in vitro and in vivo experimental evidence that SV40 LT suppresses the ubiquitin ligase function of CRL7. We show that SV40 LT, but not a CUL7 binding-deficient mutant (LTΔ69-83), impaired 26S proteasomedependent proteolysis of the CRL7 target protein insulin receptor substrate 1 (IRS1), a component of the insulin and insulin-like growth factor 1 signaling pathway. SV40 LT expression resulted in the accumulation and prolonged half-life of IRS1. In vitro, purified SV40 LT reduced CRL7-dependent IRS1 ubiquitination in a concentration- dependent manner. Expression of SV40 LT, or depletion of CUL7 by RNA interference, resulted in the enhanced activation of IRS1 downstream signaling pathways phosphatidylinositol-3- kinase/AKT and Erk mitogen-activated pathway kinase, as well as up-regulation of the downstream target gene c-fos. Finally, SV40 LT-positive carcinoma of carcinoembryonic antigen 424/SV40 LT transgenic mice displayed elevated IRS1 protein levels and activation of downstream signaling. Taken together, these data suggest that SV40 LT protects IRS1 from CRL7-mediated degradation, thereby sustaining high levels of promitogenic IRS1 downstream signaling pathways.
CRIS-Team Scopus Importer:2024-07-10

Inhibition of TRPM7 blocks MRTF/SRF-dependent transcriptional and tumorigenic activity - Voringer, Sandra; Schreyer, Laura; Nadolni, Wiebke; Meier, Melanie; Woerther, Katharina; Mittermeier, Constanze; Ferioli, Silvia; Singer, Stephan; Holzer, Kerstin; Zierler, Susanna; Chubanov, Vladimir; Liebl, Bernhard; et al. (Oncogene, 2019)
Myocardin-related transcription factors A and B (MRTFs) are coactivators of Serum Response Factor (SRF) that mediates the expression of genes involved in cell proliferation, migration and differentiation. There is mounting evidence that MRTFs and SRF represent promising targets for hepatocellular carcinoma (HCC) growth. Since MRTF-A nuclear localization is a prerequisite for its transcriptional activity and oncogenic properties, we searched for pharmacologically active compounds able to redistribute MRTF-A to the cytoplasm. We identified NS8593, a negative gating modulator of the transient receptor potential cation channel TRPM7, as a novel inhibitor of MRTF-A nuclear localization and transcriptional activity. Using a pharmacological approach and targeted genome editing, we investigated the functional contribution of TRPM7, a unique ion channel containing a serine-threonine kinase domain, to MRTF transcriptional and tumorigenic activity. We found that TRPM7 function regulates RhoA activity and subsequently actin polymerization, MRTF-A-Filamin A complex formation and MRTF-A/SRF target gene expression. Mechanistically, TRPM7 signaling relies on TRPM7 channel-mediated Mg2+ influx and phosphorylation of RhoA by TRPM7 kinase. Pharmacological blockade of TRPM7 results in oncogene-induced senescence of hepatocellular carcinoma (HCC) cells in vitro and in vivo in HCC xenografts. Hence, inhibition of the TRPM7/MRTF axis emerges as a promising strategy to curb HCC growth.
CRIS-Team Scopus Importer:2019-12-27

LPA-induced phosphorylation of Filamin A regulates association with Myocardin-related transcription factor A (MRTF-A) and cellular senescence - Konopa, Andreas; Meier, Melanie; Mühlich, Susanne (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-15

LPA receptor 1 (LPAR1) is a novel interaction partner of Filamin A that promotes Filamin A phosphorylation, MRTF-A transcriptional activity and oncogene-induced senescence - Konopa, Andreas; Meier, Melanie; Franz, Miriam; Bernardinelli, Emanuele; Vögele, Anna-Lena; Atreya, Raja; Ribback, Silvia; Roessler, Stephanie; Aigner, Achim; Singer, Kerstin; Singer, Stephan; Sarikas, Antonio; et al. (Oncogenesis, 2022)
Myocardin-related transcription factors A and B (MRTFs) are coactivators of Serum Response Factor (SRF), which controls fundamental biological processes such as cell growth, migration, and differentiation. MRTF and SRF transcriptional activity play an important role in hepatocellular carcinoma (HCC) growth, which represents the second leading cause of cancer-related mortality in humans worldwide. We, therefore, searched for druggable targets in HCC that regulate MRTF/SRF transcriptional activity and can be exploited therapeutically for HCC therapy. We identified the G protein-coupled lysophosphatidic acid receptor 1 (LPAR1) as a novel interaction partner of MRTF-A and Filamin A (FLNA) using fluorescence resonance energy transfer-(FRET) and proximity ligation assay (PLA) in vitro in HCC cells and in vivo in organoids. We found that LPAR1 promotes FLNA phosphorylation at S2152 which enhances the complex formation of FLNA and MRTF-A, actin polymerization, and MRTF transcriptional activity. Pharmacological blockade or depletion of LPAR1 prevents FLNA phosphorylation and complex formation with MRTF-A, resulting in reduced MRTF/SRF target gene expression and oncogene-induced senescence. Thus, inhibition of the LPAR1-FLNA-MRTF-A interaction represents a promising strategy for HCC therapy.
CRIS-Team WoS Importer:2023-01-13

Molecular Mechanisms to Target Cellular Senescence in Hepatocellular Carcinoma - Mittermeier, Constanze; Konopa, Andreas; Mühlich, Susanne (Cells, 2020)
Hepatocellular carcinoma (HCC) has emerged as a major cause of cancer-related death and is the most common type of liver cancer. Due to the current paucity of drugs for HCC therapy there is a pressing need to develop new therapeutic concepts. In recent years, the role of Serum Response Factor (SRF) and its coactivators, Myocardin-Related Transcription Factors A and B (MRTF-A and -B), in HCC formation and progression has received considerable attention. Targeting MRTFs results in HCC growth arrest provoked by oncogene-induced senescence. The induction of senescence acts as a tumor-suppressive mechanism and therefore gains consideration for pharmacological interventions in cancer therapy. In this article, we describe the key features and the functional role of senescence in light of the development of novel drug targets for HCC therapy with a focus on MRTFs.
CRIS-Team Scopus Importer:2020-12-11
Keywords: DLC1; HCC; MRTF; senescence; senolytics; SRF

Pro-senescence therapy for hepatocellular carcinoma - Muehlich, Susanne; Gudermann, Thomas (Aging-Us, 2013)
CRIS-Team Scopus Importer:2024-07-10

Science Signaling Podcast for 10 November 2015: Regulation of gene expression by actin dynamics - Muehlich, Susanne; VanHook, Annalisa M. (Science Signaling, 2015)
This Podcast features an interview with Susanne Muehlich, author of a Research Article that appears in the 10 November 2015 issue of Science Signaling, about how actin dynamics can regulate gene expression. The actin cytoskeleton is highly dynamic, with actin filaments polymerizing and depolymerizing to allow cells to move, divide, or maintain their shape. In the polymerized state, actin subunits are referred to as filamentous actin (F-actin), whereas soluble actin monomers are called globular actin (Gactin). Actin dynamics can influence gene expression through changes in the relative abundances of F-actin and G-actin. The transcriptional coactivator MKL1 remains in the cytoplasm when it is bound to G-actin but translocates into the nucleus when it dissociates from G-actin. In the nucleus, MKL1 cooperates with the transcription factor SRF to promote the expression of target genes. Kircher et al. found that MKL1 must also associate with the F-actin-binding protein Filamin A to stimulate target expression.
CRIS-Team Scopus Importer:2024-07-10
Keywords: Actin cytoskeleton; Cytoskeletal dynamics; F-actin; Filamin A; Gactin; Megakaryoblastic leukemia 1; MKL1; Science signaling; Serum response factor; SRF; Transcription factor

Synergistic induction of CTGF by cytochalasin D and TGF?-1 in primary human renal epithelial cells: Role of transcriptional regulators MKL1, YAP/TAZ and Smad2/3 - Muehlich, Susanne; Rehm, Margot; Ebenau, Astrid; Goppelt-Strübe, Margarete (Cellular Signalling, 2017)
Changes in cell morphology that involve alterations of the actin cytoskeleton are a hallmark of diseased renal tubular epithelial cells. While the impact of actin remodeling on gene expression has been analyzed in many model systems based on cell lines, this study investigated human primary tubular epithelial cells isolated from healthy parts of tumor nephrectomies. Latrunculin B (LatB) and cytochalasin D (CytoD) were used to modulate G-actin levels in a receptor-independent manner. Both compounds (at 0.5?M) profoundly altered F-actin structures in a Rho kinase-dependent manner, but only CytoD strongly induced the pro-fibrotic factor CTGF (connective tissue growth factor). CTGF induction was dependent on YAP as shown by transient downregulation experiments. However, CytoD did not alter the nuclear localization of either YAP or TAZ, whereas LatB reduced nuclear levels particularly of TAZ. CytoD modified MKL1, a coactivator of serum response factor (SRF) regulating CTGF induction, and promoted its nuclear localization. TGF?-1 is one of the major factors involved in tubulointerstitial disease and an inducer of CTGF. Preincubation with CytoD but not LatB synergistically enhanced the TGF?-1-stimulated synthesis of CTGF, both in cells cultured on plastic dishes as well as in polarized epithelial cells. CytoD had no direct effect on the phosphorylation of Smad2/3, but facilitated their phosphorylation and thus activation by TGF?-1. Our present findings provide evidence that morphological alterations have a strong impact on cellular signaling of one of the major pro-fibrotic factors, TGF?-1. However, our data also indicate that changes in cell morphology per se cannot predict those interactions which are critically dependent on molecular fine tuning of actin reorganization.
EVALuna2:3930

Synthesis, Characterization, and Application of Muscarinergic M-3 Receptor Ligands Linked to Fluorescent Dyes - Köckenberger, Johannes; Fischer, Oliver; Konopa, Andreas; Bergwinkl, Sebastian; Mühlich, Susanne; Gmeiner, Peter; Kutta, Roger Jan; Hübner, Harald; Keller, Max; Heinrich, Markus (Journal of Medicinal Chemistry, 2022)
Through the linkage of two muscarinergic M-3 receptor ligands to fluorescent tetramethylrhodamine- and cyanine-S-type dyes, two novel tool compounds, OFH5503 and OFH611, have been developed. Based on the suitable binding properties and kinetics related to the M-3 subtype, both ligand-dye conjugates were found to be useful tools to determine binding affinities via flow cytometric measurements. In addition, confocal microscopy underlined the comparably low unspecific binding and the applicability for studying M-3 receptor expression in cells. Along with the proven usefulness regarding studies on the M-3, subtype, the conjugates OFH5503 and OFH611 could, due to their high affinity to the M-1 receptor, evolve as even more versatile tools in the field of research on muscarinergic receptors.
CRIS-Team WoS Importer:2023-01-06

Tetraspanin 5 (Tspan5), a novel gatekeeper of the tumor suppressor dlc1 and myocardin-related transcription factors (mrtfs), controls hcc growth and senescence - Schreyer, Laura; Mittermeier, Constanze; Franz, Miriam; Meier, Melanie; Martin, Dietmar E.; Maier, Kerstin C.; Hübner, Kerstin; Schneider-Stock, Regine; Singer, Stephan; Holzer, Kerstin; Fischer, Dagmar; Ribback, Silvia; et al. (Cancers, 2021)
Human hepatocellular carcinoma (HCC) is among the most lethal and common cancers in the human population, and new molecular targets for therapeutic intervention are urgently needed. Deleted in liver cancer 1 (DLC1) was originally identified as a tumor suppressor gene in human HCC. DLC1 is a Rho-GTPase-activating protein (RhoGAP) which accelerates the return of RhoGTPases to an inactive state. We recently described that the restoration of DLC1 expression induces cellular senescence. However, this principle is not amenable to direct therapeutic targeting. We therefore performed gene expression profiling for HepG2 cells depleted of DLC1 to identify druggable gene targets mediating the effects of DLC1 on senescence induction. This approach revealed that versican (VCAN), tetraspanin 5 (TSPAN5) and N-cadherin (CDH2) were strongly upregulated upon DLC1 depletion in HCC cells, but only TSPAN5 affected the proliferation of HCC cells and human HCC. The depletion of TSPAN5 induced oncogene-induced senescence (OIS), mediated by the p16INK4a/pRb pathways. Mechanistically, silencing TSPAN5 reduced actin polymerization and thereby myocardin-related transcription factor A-filamin A (MRTF-A-FLNA) complex formation, resulting in decreased expression of MRTF/SRF-dependent target genes and senescence induction in vitro and in vivo. Our results identify TSPAN5 as a novel druggable target for HCC.
CRIS-Team Scopus Importer:2021-11-05
Keywords: DLC1; MKL1; MRTF; SRF; TSPAN5

The transcriptional coactivators megakaryoblastic leukemia 1/2 mediate the effects of loss of the tumor suppressor deleted in liver cancer 1 - Muehlich, Susanne; Hampl, V.; Khalid, S.; Singer, S.; Frank, N.; Breuhahn, K.; Gudermann, T.; Prywes, R. (Oncogene, 2012)
Deleted in Liver Cancer 1 (DLC1) is a tumor suppressor whose allele is lost in 50% of liver, breast, lung and 70% of colon cancers. Here, we show that the transcriptional coactivators Megakaryoblastic Leukemia 1 and 2 (MKL1/2) are constitutively localized to the nucleus in hepatocellular and mammary carcinoma cells that lack DLC1. Moreover, DLC1 loss and MKL1 nuclear localization correlate in primary human hepatocellular carcinoma. Nuclear accumulation of MKL1 in DLC1-deficient cancer cells is accomplished by activation of the RhoA/actin signaling pathway and concomitant impairment of MKL1 phosphorylation, which results in constitutive activation of MKL1/2 target genes. We provide evidence that MKL1/2 mediates cancerous transformation in DLC1-deficient hepatocellular and mammary carcinoma cells. Depletion of MKL1/2 suppresses cell migration, cell proliferation and anchorage-independent cell growth induced by DLC1 loss. © 2012 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2024-07-10
Keywords: DLC1; MKL1; MKL2; MRTF; Rho; SRF

The transmembrane protein tetraspanin 5 controls the effects of loss of the tumor suppressor deleted in liver cancer 1 (DLC1) on hepatocellular carcinoma (HCC) growth - Schreyer, Laura; Mittermeier, C.; Martin, D. E.; Singer, S.; Liebl, B.; Gudermann, T.; Aigner, A.; Mühlich, Susanne (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2021)
CRIS-Team WoS Importer:2021-04-23

TRPM7 kinase activity is essential for T cell colonization and alloreactivity in the gut - Romagnani, Andrea; Vettore, Valentina; Rezzonico-Jost, Tanja; Hampe, Sarah; Rottoli, Elsa; Nadolni, Wiebke; Perotti, Michela; Meier, Melanie A.; Hermanns, Constanze; Geiger, Sheila; Wennemuth, Gunther; Recordati, Camilla; et al. (Nature Communications, 2017)
The melastatin-like transient-receptor-potential-7 protein (TRPM7), harbouring a cation channel and a serine/threonine kinase, has been implicated in thymopoiesis and cytokine expression. Here we show, by analysing TRPM7 kinase-dead mutant (Trpm7 R/R ) mice, that the enzymatic activity of the receptor is not essential for thymopoiesis, but is required for CD103 transcription and gut-homing of intra-epithelial lymphocytes. Defective T cell gut colonization reduces MHCII expression in intestinal epithelial cells. Mechanistically, TRPM7 kinase activity controls TGF-β-induced CD103 expression and pro-inflammatory T helper 17, but not regulatory T, cell differentiation by modulating SMAD2. Notably, we find that the TRPM7 kinase activity promotes gut colonization by alloreactive T cells in acute graft-versus-host disease. Thus, our results unravel a function of TRPM7 kinase in T cell activity and suggest a therapeutic potential of kinase inhibitors in averting acute graft-versus-host disease.
CRIS-Team Scopus Importer:2024-07-10

Unravelling a new mechanism linking actin polymerization and gene transcription - Muehlich, Susanne; Hermanns, Constanze; Meier, Melanie A.; Kircher, Philipp; Gudermann, Thomas (Nucleus, 2016)
In the recent years, the role of actin and actin-binding proteins in gene transcription has received considerable attention. Nuclear monomeric and polymerized actin and several actin binding proteins have been detected in the mammalian cell nucleus, although their roles in transcription are just beginning to emerge. Our group recently reported that the actin-binding protein Filamin A interacts with the transcriptional coactivator MKL1 to link actin polymerization with transcriptional activity of Serum Response Factor. Here we summarize the regulation and function of MKL1, and highlight this novel mechanism of MKL1 regulation through binding to Filamin A and its implications for cell migration.
CRIS-Team Scopus Importer:2024-07-10
Keywords: actin; Filamin A; MAL; MKL1; MRTFA; SRF